Visitors perception on vandalism and safety issues in a Malaysian urban park - Nurhayati , Abdul Malek; Mariapan, Manohar (Research Centre in Public Administration and Public Services (CCASP), Academy of Economic Studies, Bucharest, Romania, 2009)
The purpose of this research is to identify and understand vandalism issues that occur in the selected case study site as well as to determine characteristics of the surrounding landscape associated with vandalism hotspots, and to justify safe environments in park areas. Questionnaire survey was conducted and specifically studies an urban park in the city of Shah Alam in the state of Selangor, Malaysia. The research indicated that people perceived vandalism to occur because of the opportunities provided by the surroundings, user behaviour, lack of security and enforcement, lack of maintenance and inspection, location and design of the facilities, and the materials used for such facilities. This research is very important because there is no other known research about perceptions of vandalism from Malaysian local park visitors’ point of view, it should help planners, park designers and park managers in local or ity councils in Malaysia, as well as the general public, to understand and expand their knowledge of vandalism in urban parks.